Omicron in Infants—Respiratory or Digestive Disease? - Anca Cristina Drăgănescu; Victor Daniel Miron; Oana Săndulescu; Anuţa Bilaşco; Anca Streinu-Cercel; Roxana Gabriela Sandu; Adrian Marinescu; Deniz Gunșahin; Karina Ioana Hoffmann; Daria Ștefana Horobeț; Daniela Pițigoi; Adrian Streinu-Cercel; et al. (Diagnostics, 2023)
The Omicron variant of SARS-CoV-2 has caused a large number of cases and hospitalizations in the pediatric population. Infants due to their age are susceptible to viral infections that may have a worse prognosis. Therefore, the aim of the current study has been to characterize the clinical features and the outcome of infants hospitalized with confirmed SARS-CoV-2 infection during the Omicron wave. We conducted a retrospective study of all consecutive infants hospitalized with symptomatic COVID-19 and no other co-infections, from January to September 2022 in one of the largest infectious diseases hospitals from Bucharest, Romania. A total of 613 infants were included in the analysis. The median age was 5 months (IQR: 3, 8 months). The clinical features were dominated by fever (96.4%), cough (64.8%) and loss of appetite (63.3%), and overall, respiratory symptoms were the most numerous (76.0%). Infants between 1-3 months old had a 1.5-fold increased risk of elevated alanine aminotransferase (ALT) values, and a longer length of hospitalization as compared to older infants. Infants between 7-9 months of age had 1.5-fold higher odds of loss of appetite, 1.7-fold more frequent cough and 1.6-fold more frequent digestive symptoms compared to infants in other age groups. The presence of digestive symptoms increased the probability of hepatic cytolysis (increased ALT) by 1.9-fold. Continued monitoring of COVID-19 among infants is very necessary, given the progressive character of SARS-CoV-2, in order to take correct and rapid therapeutic measures and to adapt to clinical changes driven by viral variant change.